Understanding the importance of home-country skills of African immigrant entrepreneurs in South Africa - Bernard Lama Ngota; Elroy Eugene Smith; Ayanda Pamella Deliwe (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aims to understand and describe the impact of home-country skills on African immigrant entrepreneurial endeavours in a host country. Furthermore, the article investigates how home-country entrepreneurial skills affect immigrant entrepreneurial motivations, activities, and outcomes. Research Design & Methods: Following an interpretivist research paradigm, we applied a qualitative research approach. We identified 12 African immigrant entrepreneurs through purposive sampling and semi-structured interviews with the participants. We then analysed the collected data using a content analysis. Findings: We observed that African immigrant entrepreneurs who migrate with skills obtained through owning or being involved in a business, and apprenticeship in their home country, are much more prepared for entrepreneurship in their host country. Furthermore, the findings suggested that African immigrant entrepreneurs associated with a family business gain entrepreneurial skills and are more ready to start up a business venture in their host country. Implications & Recommendations: The study identified a gap in the literature regarding the entrepreneurial skills and knowledge of African immigrant home-country residents in the host country context. The obtained results are useful for immigrant entrepreneurial practice, particularly for immigrants considering going international. Contribution & Value Added: It is the first study in a developing country that investigates the significance of African immigrant home-country skills in motivating entrepreneurship in the host country.
Keywords: J15; L26; M10; 330; African immigrant entrepreneurship; entrepreneurial skills; home country; entrepreneurship; African business; South Africa